Unlocking the Potential of Real-Time Data: Edge Computing Meets the Cloud - Karthikeya Achanta (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Edge computing and cloud integration have become pivotal in data-driven decision-making, particularly in domains such as the Internet of Things (IoT), smart manufacturing, and autonomous systems. This paper explores the symbiotic relationship between edge computing and the cloud, emphasizing their role in enhancing real-time data processing capabilities. Edge computing, characterized by localized data processing and analysis, brings computational resources closer to data sources, reducing latency and bandwidth requirements. Meanwhile, the cloud offers the benefits of vast storage capacity, scalability, and centralized data processing.